Sets of uniqueness, weakly sufficient sets and sampling sets for weighted spaces of holomorphic functions in the unit ball - Hu, Bingyang (2022)
We consider, in a quite general setting, inductive limits of weighted spaces of holomorphic functions in the unit ball of Cn. The relationship between sets of uniqueness, weakly sufficient sets and sampling sets in these spaces is studied. In particular, the equivalence of these sets, under some conditions of the weights, is obtained.